2016
DOI: 10.3390/ma9060489
|View full text |Cite
|
Sign up to set email alerts
|

Processing, Mechanical and Optical Properties of Additive-Free ZrC Ceramics Prepared by Spark Plasma Sintering

Abstract: In the present study, nearly fully dense monolithic ZrC samples are produced and broadly characterized from microstructural, mechanical and optical points of view. Specifically, 98% dense products are obtained by Spark Plasma Sintering (SPS) after 20 min dwell time at 1850 °C starting from powders preliminarily prepared by Self-propagating High-temperature Synthesis (SHS) followed by 20 min ball milling. A prolonged mechanical treatment up to 2 h of SHS powders does not lead to appreciable benefits. Vickers ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…The increasing interest in these materials is due to their unique combination of properties, including the highest melting points of any group of materials, >3000°C, elevate strength at extreme temperature, like 600-800 MPa at 1500-2100°C [11], high thermal conductivity, 80-110 W/mK up to 2000°C [12] and chemical stability. Recently, it has been found that most of these compounds also have the characteristic of being intrinsic solar selective materials [13][14][15][16][17][18][19], but the understanding of the optical properties of these materials is still very scanty, especially at high temperature. UHTCs have thus the potential to be suited for application in high temperature solar receivers, once their basic properties have been properly investigated and correlated to the bulk and surface characteristics.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing interest in these materials is due to their unique combination of properties, including the highest melting points of any group of materials, >3000°C, elevate strength at extreme temperature, like 600-800 MPa at 1500-2100°C [11], high thermal conductivity, 80-110 W/mK up to 2000°C [12] and chemical stability. Recently, it has been found that most of these compounds also have the characteristic of being intrinsic solar selective materials [13][14][15][16][17][18][19], but the understanding of the optical properties of these materials is still very scanty, especially at high temperature. UHTCs have thus the potential to be suited for application in high temperature solar receivers, once their basic properties have been properly investigated and correlated to the bulk and surface characteristics.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Particular emphasis was devoted to identify their correlation with relevant material characteristics, such as compositions, porosity, surface finishing. Several ultra-refractory boride and carbides have been studied in the framework of the project [13][14][15][16][17], allowing to identify the most promising materials for solar absorber applications. This work describes, as a case study, an extensive work on ZrB 2based ceramics, consolidated through different processes, with or without MoSi 2 as secondary phase, textured or with controlled porosity.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Among various preparation methods, the combustion synthesis technology has attracted much attention for its easy operation and low energy consumption 14–16 . In addition, the combustion synthesis has been widely used to combine with other routes to prepare composites containing ZrC 17–30 . As these ceramic particles are mainly derived from the combustion synthesis reaction, understanding the kinetic characteristics is vital to achieving a desired microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] In addition, the combustion synthesis has been widely used to combine with other routes to prepare composites containing ZrC. [17][18][19][20][21][22][23][24][25][26][27][28][29][30] As these ceramic particles are mainly derived from the combustion synthesis reaction, understanding the kinetic characteristics is vital to achieving a desired microstructure. Conventionally, the influence of the kinetic parameters on the combustion behaviors and synthesized products was predicted by thermodynamic calculations and/or reaction mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum processing temperatures in SPS of ZrC powder were reduced by bringing the initial particle size down into the nanometer range through ball‐milling and sol‐gel methods . The self‐propagating high‐temperature synthesis was combined with SPS to produce monolithic ZrC ceramics at relatively lower temperatures, in which the optical properties of the obtained specimens were found to be good for solar energy applications …”
Section: Introductionmentioning
confidence: 99%